Using Reflective Practice for a more Humane Higher Education - Toni, Noluthando; Makura, Alfred H (South African Journal of Higher Education, 2016)
The rationale behind the paper is to explore the importance of academics to constantly and consistently reflect on what they teach, why they teach what they teach, how they teach and assess, keeping in mind who they teach (calibre of their students), and the circumstances they teach under. Using a desktop approach, the paper delves into classroom practices, challenges and the influence of what happens ‘beyond the classroom’ on both the lecturer and students’ performance. The paper is fundamentaly a reflection of what is witnessed by the presenters themselves in their daily encounters, to a large extent, with lecturers sharing their challenges, and to a lesser extent, with students seeking development and support in their endeavours to succeed in their studies. Reflective practice is offered as a plausible approach that can be used systematically to gain a deeper understanding of the teaching and learning process in higher education.